Conservation tillage practices on weed incidence in cereal fodder production in rice fallows - Prameela, P; George, Gintu (Journal of Tropical Agriculture, 2013)
A field experiment was conducted to study the effect of various tillage practices like zero tillage, herbicide based zero tillage, minimum tillage and normal tillage on weed incidence and yield of fodder cereals in rice fallows. The population of grasses, sedges and broad leaved weeds as well as their dry weight was the highest in zero tillage. The highest forage yield was realized in herbicide based zero tillage followed by minimum tillage. The performance of maize and bajra were the best in herbicide based zero tillage, whereas performance of fodder sorghum in all the treatments except zero tillage was good. .